33=7(w+7)-3w

Simple and best practice solution for 33=7(w+7)-3w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33=7(w+7)-3w equation:


Simplifying
33 = 7(w + 7) + -3w

Reorder the terms:
33 = 7(7 + w) + -3w
33 = (7 * 7 + w * 7) + -3w
33 = (49 + 7w) + -3w

Combine like terms: 7w + -3w = 4w
33 = 49 + 4w

Solving
33 = 49 + 4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-4w' to each side of the equation.
33 + -4w = 49 + 4w + -4w

Combine like terms: 4w + -4w = 0
33 + -4w = 49 + 0
33 + -4w = 49

Add '-33' to each side of the equation.
33 + -33 + -4w = 49 + -33

Combine like terms: 33 + -33 = 0
0 + -4w = 49 + -33
-4w = 49 + -33

Combine like terms: 49 + -33 = 16
-4w = 16

Divide each side by '-4'.
w = -4

Simplifying
w = -4

See similar equations:

| n-37=0 | | 150=v+113 | | sqrt(x+1)-sqrt(9-x)=sqrt(2x-12) | | -10g^2+13g-4=0 | | 2sin^2(4x)-1=0 | | -10g+13g-4=0 | | 3x+2*2x=21 | | 3.4=3p | | 9v=ir | | 3(x-8)=-9x+12 | | 10t-11=7t-5 | | 3.3x-11.26=5.9 | | -6x-2=(3x^2+1) | | 180=28x+(x*x) | | X(4X-8)=(4X+5)(x-2) | | 9+(9+x)+(9+.5(9+x))=9+(9+x)+(9+.5(9+x)) | | 3(x+5)=2(4x+10) | | 2(x-2)=60-(1-x) | | 14=0.8x | | 3x+3x+4x-30=180 | | 5y(2x-1)=y(x+2)+20 | | 2.9x-18.31=7.5 | | x^2+22x-40=0 | | 2.2x-15.18=3.3 | | 7m-4-2m=13 | | 3.5=3(4+.5r) | | X^4-8x^3+23x^2-28x+11=0 | | x-.3x=56000 | | x+.3x=56000 | | 3.5r=3(4+.5) | | y=3x^500+15x^100 | | 3.5r=3(4+5) |

Equations solver categories